Adopting off-site construction into the Saudi Arabian construction industry. Issue 3 (27th September 2021) - Trigunarsyah, Bambang; Santoso, Try Puji; Hassanain, Mohammad A; Tuffaha, Firas
Abstract : This study examined the relationship and hierarchy among the factors that enable the adoption of off-site construction into the Kingdom of Saudi Arabia (KSA) construction industry. This study used interviews with the industry's key stakeholders to identify enablers for adopting off-site construction. A questionnaire survey of construction practitioners then verified the results. It was then followed by pairwise comparison questionnaires distributed to the interviewees to develop a model using the interpretive structural model (ISM). Ten enablers were identified from interviews, which were then verified by a questionnaire survey of construction practitioners. From the ten enablers, a hierarchical framework was formed for its implementation. The results culminated in developing an ISM for a strategy in off-site construction in the KSA. The model provides a practical framework for the relevant government authorities and other key stakeholders to focus on those factors that must be prioritised to adopt off-site construction successfully.